Acute growth hormone response to concurrent strength-sprint training with different orders in strength-trained men - Bayat, D.; Tadibi, V. (Sport Sciences for Health, 2021)
Purpose The purpose of this study was to investigate the effect of the intra-session order of concurrent strength-sprint training on the acute growth hormone response.